APLIKASI GAME EDUKASI MATEMATIKA TINGKAT DASAR BERBASIS ANDROID - Sulistyowati Sulistyowati; Eko Gunawan; Lili Rusdiana (Universitas Teknokrat Indonesia, 2022)
Game is one of the applications that are favored by children. Not a few parents who allow their children to use a smartphone with various reasons such as so that children do not interfere with work, so that children do not neglect, and various other reasons. However, sometimes smartphones are misused only for playing games by children, so the time that should be used for learning is instead used for playing games only. So that the game does not only waste the child's time in vain, then built a game application for children based on the genre of fighter and education in the game of hero against monsters accompanied by mathematics learning. The features provided in the application are 4 types of questions such as addition, subtraction, multiplication, and division as well as 6 levels of problem difficulty level. By this basic level math game it can be an alternative in learning while playing games through smartphones. This game is able to be a fun learning media in learning mathematics for game users.